Transport of skips between recycling centers and treatment facilities. (September 2022) - Wøhlk, Sanne; Laporte, Gilbert
Abstract: We study two versions of a skip pickup and delivery problem. In the first version, skips are picked up from recycling centers and, depending on their content, they are transported to specified treatment facilities where they are emptied before being returned to their origin. In the second version, the point of return of empty skips is flexible and determined by the skip type. We provide mathematical models for both versions of the problem and present a variable neighborhood search-inspired heuristic for solving them to near-optimality. Computational results are provided for real-life instances from four areas in Denmark. Highlights: A new pickup and delivery problem with three activities is proposed. The problem is based on a real-life problem of transporting skips. ILP models and valid inequalities are presented. A VNS-inspired heuristic is used to solve the problem.